Does chronic alcohol use by HIV-infected patients on d4T/3TC/NVP drug regimen effect the HIV viral load and what is the therapeutic window of the drugs, CD4+ count and WBC count in patients with high viral load during the 9 months period of follow up? - Bbosa, Godfrey S.; Anokbonggo, William W.; Kyegombe, David B.; Ntale, Muhammad; Mugisha, Apollo; Musoke, David; Ogwal-Okeng, Jasper (International Journal of Basic & Clinical Pharmacology, 2013)
The study investigated the effects of chronic alcohol use on HIV viral load in HIV-infected patients on d4T/3TC/NVP drug regimen during 9 months follow up period. It also determined plasma drug concentrations of d4T, 3TC and NVP; CD4+ and WBC counts for patients with high HIV viral load. A case-control study using repeated measures with serial measurements was used. A total of 41 patients (20 alcohol group and 21 control group) were screened for alcohol use using WHO AUDIT tool and chronic alcohol use biomarkers. Blood sampling was done at 3 month intervals for a period of 9 months. HIV viral load was determined using Roche Amplicor HIV-1 monitor test, version 1.5 (Amplicor). The d4T, 3TC and NVP concentrations were determined by Shimadzu Class-VPTM HPLC Chromatography data system version 6.1. The CD4+ cell count was determined using FACSCalibur flow cytometer. The WBC was determined using automated hematological Coulter CBC-5 Hematology Analyzer system. Results show that % patients with HIV viral load ≥400 copies/ml in control group was highest (23.8%, n=5) at 3 month while in chronic alcohol use group, it was at 0 month (35%, n=7) for both WHO AUDIT tool and chronic alcohol-use biomarkers groups. Generally patients with high viral load ≥400 copies/ml was observed in chronic alcohol use as compared to control group in both WHO AUDIT tool and biomarkers group despite of patients having high steady state d4T, 3TC and NVP plasma drug concentrations in circulation that is available to suppress HIV virus. The high viral load could be associated with the emergence of resistance of the HIV virus and these patients generally had a low CD4+ cell count. Some of these patients had no detectable d4T plasma drug concentrations in circulation and most of them with high viral load had sub-therapeutic NVP plasma drug concentrations in their blood circulation. Chronic ethanol use by HIV-infected patients on d4T/3TC/NVP drug regimen increased HIV viral load and the patients with high viral load had sub-therapeutic NVP plasma drug concentrations and some with undetectable d4T drug concentrations in their blood circulation.
Keywords: Chronic alcohol use; Plasma; HIV viral load; d4T/3TC/NVP regimen